2011
DOI: 10.1007/s11095-011-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacokinetics and Biodistribution of Human Papillomavirus DNA Vaccine Delivered in Human Endogenous Retrovirus Envelope-Coated Baculovirus Vector

Abstract: HPV16L1 delivered via AcHERV resides longer in the body than HPV16L1 in naked form. The lack of tissue tropism ensures the safety of AcHERV vectors for further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…In the study, the distribution levels of intramuscularly administered AcHERV encoding HPV16L1 were similar among the brain, heart, and lung tissues. Similar to our previous report [ 24 ], the brain distribution of porcine-derived adeno-associated virus was observed following intravenous injection to mice [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the study, the distribution levels of intramuscularly administered AcHERV encoding HPV16L1 were similar among the brain, heart, and lung tissues. Similar to our previous report [ 24 ], the brain distribution of porcine-derived adeno-associated virus was observed following intravenous injection to mice [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Rather, there exists a possibility that systemically absorbed AcHERV-triHPV might distribute to the brain passing the blood-brain barrier. Indeed, we previously observed the brain distribution of AcHERV encoding HPV16L1 following intramuscular administration [ 24 ]. In the study, the distribution levels of intramuscularly administered AcHERV encoding HPV16L1 were similar among the brain, heart, and lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Baculoviruses have properties that other vectors lack, such as an inability to replicate in mammalian cells, a capability to accommodate large amounts of foreign DNA and the ability to transduce a wide variety of mammalian cells both in vitro and in vivo . Excluding vaccination and ex vivo studies , thus far, most preclinical animal studies where baculovirus has been applied for direct gene transfer in vivo have been performed using only reporter genes such as LacZ , green fluorescent protein or luciferace in mice and rats . In the present study, we showed that baculovirus also has potential for therapeutic gene transfer in a large animal model.…”
Section: Introductionsupporting
confidence: 48%
“…First, the entrapment of antigen gene in the recombinant baculoviral vector can improve the in vivo stability and significantly alter pharmacokinetic behavior. In our previous study, we reported that the mean residence times of human papillomavirus 16 L1 gene delivered in AcHERV baculoviral vector were 4.8 and 272.2-fold higher than naked human papillomavirus 16 L1 DNA vaccines [ 34 ]. Secondly, the existence of HERV moiety on the surface of the baculoviral vector can enhance the cellular uptake and antigen expression in the cells.…”
Section: Discussionmentioning
confidence: 99%